The Influence of Zakat Infaq and Shadaqah, Economic Growth and Population on the Human Development Index in North Sumatra Province - Aisyah, Siti; Tambunan, Khairina; Ilhamy Nasution, Muhammad Lathief (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2025)
This study aims to examine how zakat, infaq, and shadaqah (ZIS), economic growth, and population affect the Human Development Index (HDI) in North Sumatra Province. The background of this research lies in the persistent disparity of human development across regions and the lack of empirical studies that integrate Islamic social finance variables, such as ZIS, into human development analysis. The study employs a quantitative research design with a panel data regression method using the Fixed Effect Model (FEM). The sample consists of eight cities in North Sumatra (Medan, Binjai, Pematang Siantar, Tebing Tinggi, Tanjung Balai, Sibolga, Padangsidimpuan, and Gunung Sitoli) covering the 2018–2021 period. Data were obtained from the Central Statistics Agency (BPS) and the National Zakat Agency (BAZNAS). The findings show that ZIS has a positive but insignificant effect on the HDI, suggesting that the distribution of ZIS funds has not yet optimized its impact on human development. Economic growth has a significant negative effect on HDI, indicating that growth in North Sumatra remains non-inclusive and unevenly distributed. Meanwhile, the population variable has a negative but insignificant influence, implying that population growth has not been matched by improvements in quality. Simultaneously, the three variables explain 93.13% of the variation in HDI. Based on these results, the study recommends that policymakers and Islamic financial institutions enhance ZIS management by prioritizing empowerment-based programs rather than consumptive aid. Regional governments should also focus on inclusive economic growth, human resource quality improvement, and equitable access to education and healthcare as part of integrated human development strategies.